REVIEW ON CELLULAR SIGNALING, GROWTH FACTORS, AND MECHANICAL STIMULUS IN NERVE REGENERATION - Ezegbe Chekwube Andrew; Amarachi Grace Ezegbe (Universal Journal of Pharmaceutical Research, 2025)
The autonomous and peripheral constitute the entire nervous system. Peripheral nerve injury caused by trauma, accident and other associated factors always results in a huge loss of both the sensory and motor functions. The injured nerves can be successfully restored through the rebuilding of the functional axons. The complete recovery of PNI has not been optimized. Exogenous growth factor (GF) is a new therapeutic strategy that can be used in nerve regeneration. Growth factors mechanism of action is based on the ability to activate the signaling cascades via binding to the individual receptors in order to exert the multiple effects and restore the neuron and tissue regeneration. Although the GFs are limited by their short half-life and rapid deactivation. The use of nerve conduits has been able to reduce these limitations. The nerve conduits have been good biocompatibility and biofunctionality properties. Peer Review History: Received 14 September 2024; Reviewed 18 November 2024; Accepted 23 December; Available online 15 January 2025 Academic Editor: Dr. Muhammad Zahid Iqbal , AIMST University, Malaysia, drmmziqbal@gmail.com Reviewers: Dr. Vanina Doris Edo’o, University of Yaounde I, Yaounde, Cameroun, vanina_edoo@yahoo.com Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com